ADAPTASI BENTUK ARSITEKTUR VERNAKULAR PADA HUNIAN PERKOTAAN KOLONIAL GORONTALO - Muhamad Rainaldy Putra Makale; Iwan Sudradjat (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2023)
Abstract: The arrival of the Dutch to Gorontalo instigated the interaction between the Dutch colonial culture and the culture of the local people. One of the modes of cultural interaction is the adaptation of Gorontalo's vernacular architectural forms to the houses where the Dutch lived in urban areas. The adaptation process occurred to meet the demands of everyday life and adapt to climatic conditions and the surrounding environment. The adaptation of Gorontalo's vernacular architectural forms occurs in dwellings located in colonial government areas, where the physical appearance clearly shows a meeting between European/Dutch architectural elements and local Gorontalo architectural elements. The adaptation of Gorontalo's vernacular architectural forms to the Dutch houses in urban areas during the colonial period also determined the further development of the character and identity of the city of Gorontalo. This study aims to identify the various forms of Gorontalo vernacular adaptations carried out by the Dutch in their dwellings and their implications for developing the character and identity of the city of Gorontalo. The research area covers the administrative center area of the assistant resident during the colonial era, now known as the urban center of Gorontalo. The research utilizes a qualitative descriptive method supported by literature and field observation data. The results confirmed that the interaction between the Dutch colonial culture and the culture of the local community has led to the adaptation of Gorontalo's vernacular architectural forms to the houses where the Dutch lived in urban areas and significant changes in the socio-cultural and political aspects of the city of Gorontalo.Abstrak: Kedatangan orang Belanda ke Gorontalo telah menyebabkan terjadinya interaksi antara budaya kolonial Belanda dengan budaya masyarakat lokal. Salah satu modus dari interaksi budaya tersebut adalah adaptasi bentuk arsitektur vernakular Gorontalo pada rumah tempat tinggal orang Belanda di perkotaan. Proses adaptasi dilakukan dalam upaya memenuhi tuntutan kehidupan sehari-hari dan menyesuaikan diri dengan kondisi iklim dan lingkungan sekitar. Adaptasi bentuk arsitektur vernakular Gorontalo tersebut tampak pada hunian yang berlokasi di kawasan pemerintahan kolonial, di mana tampilan fisiknya jelas memperlihatkan adanya pertemuan antara unsur arsitektur Eropa/ Belanda dengan unsur arsitektur lokal Gorontalo. Adaptasi bentuk arsitektur vernakular Gorontalo pada rumah tempat tinggal orang Belanda di perkotaan pada masa kolonial turut menentukan perkembangan karakter dan identitas kota Gorontalo selanjutnya. Penelitian ini bertujuan untuk mengidentifikasi ragam bentuk adaptasi vernakular Gorontalo yang dilakukan orang Belanda pada huniannya serta implikasinya terhadap perkembangan karakter dan identitas kota Gorontalo. Penelitian dilakukan di wilayah pusat pemerintahan asisten residen pada masa pemerintahan kolonial, yang kini dikenal sebagai pusat perkotaan Gorontalo. Penelitian dilakukan dengan metode deskriptif kualitatif, didukung oleh studi pustaka dan data pengamatan lapangan. Hasil penelitian menunjukkan bahwa interaksi antara budaya kolonial Belanda dengan budaya masyarakat lokal tidak hanya menyebabkan terjadinya adaptasi bentuk arsitektur vernakular Gorontalo pada rumah tempat tinggal orang Belanda di perkotaan, tetapi juga perubahan yang signifikan pada aspek sosial budaya dan politik kota Gorontalo.